Inclusive Approach for Quality and Safety Environment Improvement in Oil and Gas Industry - Mochammad Wahyu Ghani; Marya Yenita Sitohang (Journal of Indonesian Social Sciences and Humanities, 2020)
Implementing safety behavior in the oil and gas industries is still challenging, although fatal accidents often occur. This research aims to analyze how SHEQ talks, a Badak LNG program, can successfully prevent workers' work accidents. Using qualitative methods with a case study approach, the researchers interviewed several key persons in the SHEQ talk program, including the board of management, the SHEQ department's employees, and Badak LNG's employers. Inclusiveness is the main component in the SHEQ talks program. It leads to safety behavior among all Badak LNG's workers (interdependent stage). Unlike the usual behavior-based safety program, SHEQ talks encourage all employees to have good knowledge and skill of health and safety environments. Therefore, safety performance among the workers does not entirely depend on the OSH officers. Eliminating the superior and subordinate when conducting the safety talks are essential to build the safety culture among workers in the oil and gas industries.